D DAMPAK AKTIVITAS TAMBANG NIKEL TERHADAP KONDISI EKONOMI MASYARAKAT DI KECAMATAN MOLAWE KABUPATEN KONAWE UTARA - Irmawatty Tamburaka; Apoda Apoda (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The mining sector is one of the main pillars of economic development in Indonesia, particularly in regions with abundant natural resources. North Konawe Regency, in the Southeast Sulawesi Province, is one of the areas with the largest nickel reserve potential in Indonesia. Specifically, Molawe District has become a center for intensive nickel mining activities due to the presence of several Mining Business Licenses (IUP) operating in the region. This study aims to examine the impact of nickel mining activities on economic conditions in Molawe District, North Konawe Regency. The sample in this study consisted of 73 respondents, selected using a simple random sampling technique. The data analysis method used is descriptive analysis, utilizing both primary and secondary data sources. The research findings reveal that nickel mining activities in Molawe District bring economic benefits in the form of employment opportunities and increased income. However, they also cause negative impacts related to changes in livelihoods, environmental degradation, and potential social conflicts. Sustainable management, strict government supervision, and corporate compliance with environmental standards are essential to minimize these negative impacts.